Aortic aneurysms: Replacing the ascending aorta and aortic valve with a composite valved tube with restoration of the coronary circulation - Filgueira, José Luis; Scola, Ramón; Stanham, Roberto; Estable, Héctor; Estigarribia, Jorge; Battistessa, Sergio; Cassinelli, Mauricio (Cirugía del Uruguay, 1986)
Our experience with 10 patients wilh ascending aortic aneurysms is exposed. They were treated with a composite technique of valved tube graft. The coronary circulation was restablished with coronary arteries by pass grafts with saphenous vein or by the implant of the coronary ostium to the dacron tube. Patients with non dissecting aneurysrns (annulo aortic ectasia. Marfan and congenit) and dissecting aneurysrns (De Bakey type I or type II) of ascending aorta are included. Pathology showing the lesional extent in each case is analyzed. Technical details and results are exposed. A cornparative study between this serie and others authors results is done.